2014
DOI: 10.1111/srt.12144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the regional environment on the skin properties and the early wrinkles in young Chinese women

Abstract: In the Chinese women aged 20-35 years, the skin was influenced by the climates, so they had regionally a different skin. The skin hydration, sebum contents, TEWL, and pH can affect the early wrinkle formation than skin elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In addition, a study of Japanese women confirmed that fine wrinkles and an uneven skin texture increase when the skin is exposed to a low humidity and then a high humidity [5]. In a previous study, we reported that exposure to a dry environment can cause premature aging by inducing fine wrinkles in the eye rims of young women [6]. Since temperature also affects skin, TEWL increases when the ambient temperature increases, whereas it decreases when RH increases.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, a study of Japanese women confirmed that fine wrinkles and an uneven skin texture increase when the skin is exposed to a low humidity and then a high humidity [5]. In a previous study, we reported that exposure to a dry environment can cause premature aging by inducing fine wrinkles in the eye rims of young women [6]. Since temperature also affects skin, TEWL increases when the ambient temperature increases, whereas it decreases when RH increases.…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that, for example, for Asians the appearance of wrinkles and pores can be different depending on precise ethnicity, for example, Chinese, Thai, or Japanese . Moreover, even within China it was found that there were differences in wrinkle establishment depending on location and regional climate conditions in young women . The same is true for skin color characteristics which were found to differ significantly between Koreans and Cantonese subjects .…”
Section: Discussionmentioning
confidence: 98%
“…14 Studies in the Guangdong region were opportunities to complete objective evaluation criteria with new clinical signs linked to sun exposure and less noticed in previously investigated Asian cities of northern latitudes. 15 …”
Section: Methodsmentioning
confidence: 99%